2021
DOI: 10.1021/acs.organomet.1c00194
|View full text |Cite
|
Sign up to set email alerts
|

Wrapping Rhodium in a Borane Canopy: Implications for Hydride Formation and Transfer

Abstract: The unique reactivity of metal hydrides has encouraged considerable advances in both synthesis and catalysis. In this arena, ligand optimization has played a significant role, wherein metal−ligand cooperativity can be employed to guide reactivity. Of the organometallic hydride donors, rhodium(I) bis(diphosphine) compounds are known to be among the strongest with hydricity (ΔG H − ) values near that of conventionally used reducing agents: e.g., trialkyl-substituted borohydrides (ΔG H − ≈ 26 kcal mol −1 for [HBE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…102,103 In a series of studies, the authors coordinated this ligand to several late-transition metals including nickel (Ni), 104,105 cobalt (Co), 106 and rhodium (Rh). 107 To follow, this tutorial highlights differential reactivity witnessed between such P 2 B Cy4 -ligated compounds and their ''carbon-only''-substituted analogues.…”
Section: Tetraboranyl Diphosphine Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…102,103 In a series of studies, the authors coordinated this ligand to several late-transition metals including nickel (Ni), 104,105 cobalt (Co), 106 and rhodium (Rh). 107 To follow, this tutorial highlights differential reactivity witnessed between such P 2 B Cy4 -ligated compounds and their ''carbon-only''-substituted analogues.…”
Section: Tetraboranyl Diphosphine Ligandsmentioning
confidence: 99%
“…Primary efforts focused on reaction of [Rh(P 2 B Cy4 ) 2 ] + with n-BuLi, a known method to deliver Rh-H units following 1-butene eliminination. 107 Density functional theory determined that the thermodynamic site of hydride transfer was at rhodium(I) and not at boron. This contribution suggests that the boron-rich SCS is a convenient placeholder for reactive hydride equivalents.…”
Section: Tetraboranyl Diphosphine Ligandsmentioning
confidence: 99%
“…(1) 12 (dnppe = 1,2-bis(di-n-propylphosphino)ethane) was first screened as a structural isostere devoid of borane functionality (Figure 4). Exposure of a degassed THF solution of 1 to 1 atm of dry O2 resulted in a lightening of its dark orange color.…”
Section: Experimental Workmentioning
confidence: 99%
“…In a recent contribution, we reported on the synthesis of a rhodium(I) bis(diphosphine) compound, [Rh I (P2B Cy 4)2]BPh4 (1) (P2B Cy 4 = 1,2-bis(di(3-dicyclohexylboraneyl)propylphosphino)ethane) that was found to be reactive toward nucleophiles (hydride and alkyl anions), undergoing functionalization at its boron-rich SCS and not at rhodium. 12 This report was particularly thought-provoking given the similarity in hydride Å. 5 Taking the interacting and non-interacting isomers, an energy difference (DE) of +0.4 kcal mol -1 was calculated with a barrier height ((DE † ) taken as the energy difference between the lowest and highest energy isomer) of only +2.4 kcal mol -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade the use of a Lewis acidic borane as a supporting moiety 4 has proven to be an effective strategy in bolstering first-row transition metal-based H 2 and hydride reactivity. 5 We have found that bonding a heavy group 13 center (Al, Ga, In) to a d 10 nickel atom engenders catalytic hydrogenation reactivity. 6,8 b Despite precedence in the literature, 7 the Ni–B pairing has until now remained elusive in our double-decker ligand scaffold, [N(( o -C 6 H 4 )NCH 2 P i Pr 2 ) 3 ] 3− (abbrev.…”
mentioning
confidence: 99%